2016
DOI: 10.1103/physrevlett.117.048001
|View full text |Cite
|
Sign up to set email alerts
|

Water Dielectric Effects in Planar Confinement

Abstract: We investigate the dielectric profile of water confined between two planar polar walls using atomistic molecular dynamics simulations. For a water slab thickness below 1 nm the dielectric response is highly asymmetric: while the parallel component slightly increases compared to bulk, the perpendicular one decreases drastically due to anticorrelated polarization of neighboring water molecules. We demonstrate the importance of the dielectric contribution due to flexible polar headgroups and derive an effective d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
282
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(315 citation statements)
references
References 58 publications
29
282
1
3
Order By: Relevance
“…Yet, apart from non-trivial complications, the required increase of density or pressure is known to increase the dielectric constant in the limit of homogeneous liquid bulk water, 57 which connects with the previous argument about enhanced polarization fluctuations at the interface as a possible origin of the charge-stabilization in NCW. Finally, we note that it has been recently shown 30 that water confined by soft interfaces shows only a very small enhancement of ε ∥ , in stark contrast to the strikingly pronounced enhancement of ε ∥ that has been demonstrated repeatedly for water at hard interfaces. 2729,55 This clearly suggests that water confined by hard surfaces, such as mackinawite sheets in the present case, possesses distinctly different properties from water confined in soft media.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Yet, apart from non-trivial complications, the required increase of density or pressure is known to increase the dielectric constant in the limit of homogeneous liquid bulk water, 57 which connects with the previous argument about enhanced polarization fluctuations at the interface as a possible origin of the charge-stabilization in NCW. Finally, we note that it has been recently shown 30 that water confined by soft interfaces shows only a very small enhancement of ε ∥ , in stark contrast to the strikingly pronounced enhancement of ε ∥ that has been demonstrated repeatedly for water at hard interfaces. 2729,55 This clearly suggests that water confined by hard surfaces, such as mackinawite sheets in the present case, possesses distinctly different properties from water confined in soft media.…”
Section: Discussionmentioning
confidence: 46%
“…26 In particular, several studies revealed the highly inhomogeneous and anisotropic nature of the polarization fluctuations of interfacial 2729 and nanoconfined 21 water, but so far no direct link has been established between these observations and the fact that some physical/chemical processes in nanoconfined water differ greatly from those in the bulk regime. Moreover, similar studies 30 of water confined by soft interfaces show remarkably different results compared to what is observed in water at hard interfaces. 2729 This observation strongly indicates that the vast existing experimental knowledge about water under soft confinement conditions, using e.g.…”
Section: Introductionmentioning
confidence: 69%
“…In particular, for the DH and PB models, we consider, for the dielectric constant of the solvent, both the bulk value for water and a value (arbitrarily) reduced by an order of magnitude. This allows us to account for, in a simple manner, the change in the dielectric response of water at an electrified interface and under confinement, even though such a response is more complex because of, in particular, the symmetry breaking induced by the walls [78][79][80][81][82] and may result in an unexpected enhancement of permittivity in specific geometries [83].…”
Section: Resultsmentioning
confidence: 99%
“…Huang et al experimentally measured the mean-square displacement of a 1-µm-diameter silica sphere in water using optical trapping technique and found that the particle motion cannot be described by conventional theory until sufficiently long time [14]. We note that, a majority of kinetic and dynamic processes related to molecules take place in nanoscale space [1][2][3][19][20][21][22] and accomplish in just several picoseconds [23,24], such as self-assembling [25][26][27][28][29], triggering chemical reaction [7,30], intercellular signal transduction [31], and neurotransmission [32]. Unfortunately, there is rare report on the unconventional behavior in the free motion of the molecules/nanoparticles solely under thermal fluctuations within short time at the nanoscale.…”
mentioning
confidence: 74%